Analyzing Reading Activities of Montessori-Based Instruction Method for Primary Students in Singaraja Montessori School - Milala, Natariana Br; Ratminingsih, Ni Made; Santosa, Made Hery (Jurnal Penelitian Mahasiswa Indonesia, 2024)
Reading is a crucial foundational skill that all students acquire, as it is necessary for all learning activities. Reading is a basic skill that students must acquire in education, especially early learners. This study aims to analyze what reading activities use the Montessori method at Singaraja Montessori School and how the teacher carries out these activities. A qualitative descriptive method was used, and data collection was carried out through documentation, class observations, and interviews. Data were analyzed using the Thematic analysis model by Braun and Clarke (2006), which involves six steps: familiarizing data, generating initial codes, searching for themes, reviewing themes, defining themes, and producing the report. The findings show five reading activities using the Montessori method: phonic knowledge, syllable knowledge, picture cards, reading comprehension, and reading in the corner. Activities are carried out in three stages: pre-activity, whilst-activity, and post-activity. In implementation, personalized and self-directed learning are used as strategies to adapt to students' needs. This study concludes that reading activities implemented using Montessori-based instruction are designed to gradually support children's reading development in accordance with the principles of Montessori education, which emphasize independent learning and exploration.